内服中止後も発作が続いたアンギオテンシンII受容体拮抗薬とDPP4阻害薬による血管性浮腫の1例(Case of recurrent angioedema after discontinuation of angiotensin II receptor antagonists and DPP4 inhibitor). Issue 2 (18th February 2021) - (Sayumi Imamura), 今村 沙弓; (Tomoya Hirose), 廣瀬 智也; (Takashi Noma), 野間 貴之; (Yoshihito Ogawa), 小川 新史; (Tomoki Yamada), 山田 知輝; (Haruhiko Nakae), 中江 晴彦; (Yasuaki Mizushima), 水島 靖明
ABSTRACT: Angiotensin converting enzyme (ACE) inhibitor and Angiotensin II Receptor Blocker (ARB) can cause angioedema. DPP4 inhibitors alone are unlikely to cause angioedema, but the use of DPP4 in combination with ACE inhibitors was reported to exacerbate angioedema. We report a case of angioedema that repeated for several months after discontinuation of ARB and DPP4 inhibitors. The patient was a 65–year–old man who had been taking linagliptin and azilsartan for 3 years. The patient was admitted with swelling of the tongue. This condition recurred 6 times over a 98–day period after discontinuation of linagliptin and azilsartan. Angioedema recurs in about half of patients treated with ACE inhibitors even when the offending medication is discontinued. However, the majority of patients experience their first recurrence within 1 month after discontinuation, recurrence is considered to be rare 3 months after drug change. Our case shows that ARB–induced angioedema may also recur for about 3 months. 要旨: アンギオテンシン変換酵素（ACE）阻害薬およびアンギオテンシンII受容体拮抗薬（ARB）は血管性浮腫の原因となる薬剤である。DPP4阻害薬は単独では血管性浮腫を来しにくいが，ACE阻害薬と併用すると血管性浮腫を増悪させるとの報告がある。今回我々は，ARBとDPP4阻害薬併用により血管性浮腫が薬剤中止後も約3か月持続した症例を経験したため報告する。症例は65歳の男性。3年前からアジルサルタン，リナグリプチンを内服していた。舌の腫脹を主訴に来院した。薬剤中止により症状は改善したが，中止後98日目までに6回の再発を繰り返した。ACE阻害薬による血管性浮腫は原因薬剤を中止しても約半数で再発し，うち大多数は中止後1か月の間に初回の再発を経験し，薬剤変更後3か月を経過すると再発は稀とされる。今回報告する症例から，ARBとDPP4阻害薬の併用例においても同様に薬剤中止後も3か月程度再発する可能性があり，注意を要する。